Addition of gonadotropin releasing hormone antagonist for women undergoing intrauterine insemination: a randomized controlled trial - Gopal, Lakshmi; Sudhakar, Pradeepa; Kandaswami, Dhanabagyam; Manivannan, Saranya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Intrauterine insemination (IUI) is a widely acceptable fertility treatment modality. GnRH antagonists have been proven effective in restricting the LH surge. The aim of the study was to assess whether the addition of gonadotropin releasing hormone antagonist (Cetrorelix) would improve clinical pregnancy rate in women undergoing IUI. Methods: This prospective randomized controlled trial was conducted at a Sudha fertility center where 730 women with primary or secondary infertility were subjected to controlled ovarian stimulation with tablet letrozole 5mg once daily for 5 days and then human menopausal gonadotrophins 75 IU/150 IU administered intramuscularly for both the groups and for study group alone Cetrorelix (0.25 mg/day, started when the leading follicle was ≥16 mm; GnRH antagonist) was given additionally. A double insemination was performed at 36 hours and 60 hours after hCG was given (5,000 IU, intramuscularly) in both groups. Chi-square and independent t test was done. Results: Baseline characteristics in both the groups were almost equal without any statistically significant difference. Significant difference (p=0.017) was found on calculating with statistics among both groups on analyzing LH on hCG day. Clinical pregnancy rates (29.3%) were higher among the study group compared with the control group (21.7%). Conclusions: From the present study results it shows that addition of GnRH antagonists to controlled ovarian stimulation IUI significantly decreases the incidence of premature luteinization and increases the clinical pregnancy rates and live birth rate.